Assessment of The Total Oxıdant Levels In People Wıth Dıfferent Lıfestyle In Al-Diwaniyah - Al-Malıkı, Zaıd; Al-Delfi, Mohammed; Eyüpoğlu, Volkan (Journal of Biomedicine and Biochemistry, 2023)
Background Reactive oxygen species (ROS) are formed as a result of different metabolic reactions that occur normally in the human body, these free radicals harm the cell DNA, and other cellular structures and represent a waste product that must be eliminated from the body. Lipid peroxidation is one of the major outcomes of free radical-mediated injury that directly damages membranes and generates a number of secondary products in- cluding aldehydes such as MDA, which is the most abundant individual aldehyde, resulting from lipid peroxidation.Objective The purpose of this study is to Evaluate the total oxidant levels among people with different social classes in the Al-Diwaniya pop- ulation, Iraq. The possible relationship among serum of SOD, MDA and CRP in patients with obesity to identify the difference in the levels of total antioxidants with people having different lifestyles.Materials and Method Samples were obtained from the Department of Medical Laboratories and Internal Medicine Patients registered with the clinic at Diwaniyah General Hospital Between February 1 and April 1, 2021. Blood samples were used to analyze biochemical properties of serum, such as SOD and MDA.It was evaluated in patients using ELISA technology. Statistical analysis was carried out using GraphPad Prism 9.2.0.Results Our study in MDA (P-Value